A Comparative Analysis of Biochemical Indicators for air pollution in three Species Tree Planted Within the Greenbelt Project in Karbala province, Iraq - Jaafar H. Al-Hamd; Sada N. Jasim (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
This study was undertaken to represent the December 2023 (Winter) and July 2024 (Summer) within the administrative confines of Karbala governorate, as part of the Southern Greenbelt Project. Three segments of the green belt were chosen to exemplify the environmental diversity of the area. The research report examined three extensively cultivated plant species in the study area: olive (Olea europaea), eucalyptus (Eucalyptus camaldulensis), and date palm (Phoenix dactylifera), to evaluate their efficacy in tolerating air pollution. Plants underwent APTI analysis using four biochemical parameters: total chlorophyll concentration, pH, relative water content (RWC), and ascorbic acid levels. This research aims to evaluate the tree species planted in the Southern Green Belt Project and to compare their effectiveness in mitigating air pollution, assessing their appropriateness for greenbelt initiatives. The aim of the research is to examine the efficacy of these plants in tolerating air pollutants. The findings indicated a substantial disparity between the locations and the seasons. The Air Pollution Tolerance Index for the eucalyptus plant had the highest APTI value, followed by the olive and palm species. The December 2023 yields superior outcomes compared to July 2024 for all plants. The distinction among plants based on the intensity of pollution to which they are subjected and the varying temperatures between seasons.